2023
DOI: 10.1097/j.pain.0000000000002911
|View full text |Cite
|
Sign up to set email alerts
|

Identifying chronic low back pain phenotypic domains and characteristics accounting for individual variation: a systematic review

Abstract: Interpatient variability is frequently observed among individuals with chronic low back pain (cLBP). This review aimed at identifying phenotypic domains and characteristics that account for interpatient variability in cLBP. We searched MEDLINE ALL (through Ovid), Embase Classic and EMBASE (through Ovid), Scopus, and CINAHL Complete (through EBSCOhost) databases. Studies that aimed to identify or predict cLBP different phenotypes were included. We excluded studies that focused on specific treatments. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 105 publications
1
2
0
Order By: Relevance
“…Sample sizes varied across studies significantly (eg, 24–1037 participants). For chronic LBP, the most identified phenotypic domains accounting for variability among patients included psychological and behavioral domains, similar to our findings, in addition to social, sensory profiling, and pain‐related characteristics and pain impact domains 56 . Much less work has been focused on cohorts with varying acuity of symptoms (eg, acute, subacute, and chronic).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Sample sizes varied across studies significantly (eg, 24–1037 participants). For chronic LBP, the most identified phenotypic domains accounting for variability among patients included psychological and behavioral domains, similar to our findings, in addition to social, sensory profiling, and pain‐related characteristics and pain impact domains 56 . Much less work has been focused on cohorts with varying acuity of symptoms (eg, acute, subacute, and chronic).…”
Section: Discussionsupporting
confidence: 84%
“…Numerous studies have conducted phenotyping analyses in patients with LBP using a variety of methods and patient‐level variables 27,53–55 . For chronic LBP specifically, a recent systematic review found 43 studies, 56 with the number of phenotypes identified ranging from two to nine per study 54,56 . The large majority of studies identified three to four phenotypes 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation